REVITALISASI STUDI HADIS TEMATIK: UPAYA MENJAWAB TANTANGAN ZAMAN - Atikah (Al-Hasyimi - Jurnal Ilmu Hadis, 2025)
Thematic hadith study (dirāsah mawḍū‘iyyah) is a methodological approach that analyzes hadiths based on specific themes, enabling a more comprehensive and contextual understanding of prophetic traditions. This approach emerges in response to the limitations of traditional hadith studies, which often emphasize textual and sanad analysis while neglecting the social realities surrounding the text. In today’s era, Muslims face a range of modern challenges, including moral crises, environmental degradation, social inequality, and the spread of religious misinformation. Therefore, revitalizing thematic hadith studies is an urgent need to position hadith as a living and applicable source of values. This article aims to explore the definition, historical development, and the urgency of renewing thematic hadith studies in responding to contemporary issues. Using a qualitative library research method with a descriptive-analytical approach, this study finds that revitalization can be achieved through interdisciplinary integration, particularly with social sciences and humanities, and the use of digital technology in hadith exploration and dissemination. This approach offers great potential for re-establishing hadith as a foundation for social ethics, justice, and religious moderation in modern contexts. The findings are expected to contribute both theoretically and practically to the development of a more progressive and relevant hadith scholarship